Occupational Safety and Health : Fundamental Principles and Philosophies - Reese, Charles D. (CRC Press, Taylor & Francis Group, 2017)
Most occupational safety and health books explain how to apply concepts, principles, elements, tools of prevention and develop interventions, and initiatives to mitigate occupational injuries, illnesses and deaths. This is not a how-to book. It is a book that addresses the philosophical basis for all of the varied components and elements needed to develop and manage a safety and health program. It is a book designed to answer the questions often posed as to why should we do it this way. It is the “Why” book and the intent is to provide a blueprint and a helpmate for the philosophical basis for occupational safety and health and the justification as an integral component of doing business